Comparison of long-term efficacy between biological agents following tumor necrosis factor inhibitor failure in patients with rheumatoid arthritis: a prospective cohort study. (November 2021) - Bogas, Patricia; Plasencia-Rodriguez, Chamaida; Navarro-Compán, Victoria; Tornero, Carolina; Novella-Navarro, Marta; Nuño, Laura; Martínez-Feito, Ana; Hernández-Breijo, Borja; Balsa, Alejandro
Background: Currently, there is contradictory evidence regarding the best strategy to follow after discontinuation of a first biological agent in patients with rheumatoid arthritis (RA). We aimed to compare the long-term efficacy of switching to a second tumor necrosis factor inhibitor (TNFi) versus biopharmaceuticals with other mechanisms of action (non-TNFi) in patients with RA who previously failed a first TNFi. Methods: This prospective cohort study analyzed data from 127 patients who discontinued a previous TNFi between 1999 and 2016. Disease activity was assessed at baseline and at 6, 12, and 24 months (m-6, m-12, m-24) after switching. Primary outcome was the proportion of patients achieving good/moderate EULAR response (E-resp). Factors associated with clinical outcomes were assessed using univariate and multivariate logistic regression models. Results: Seventy-seven (61%) patients received a second TNFi and 50 (39%) switched to a non-TNFi. At m-6 and m-12, no differences were observed between groups; nevertheless, at m-24, the proportion of patients with E-resp was higher in the non-TNFi group (49% TNFi group versus 77% non-TNFi group; p  = 0.002). In regression models, switching to a non-TNFi was significantly associated with E-resp at m-24 (odds ratio = 3.21; p  = 0.01). When assessing the response to the second biological agent based on the reason for discontinuation of the first TNFi, similar results were obtained; at m-24, patients who discontinued the first TNFi due to inefficacy (either primary or secondary) experienced a better E-resp if they had switched to a non-TNFi (primary inefficacy: 52% TNFi group versus 79% non-TNFi group, p  = 0.09; secondary inefficacy: 50% versus 76%, p  = 0.03). Conclusion: In our cohort of RA patients who discontinued a first TNFi, those who switched to a non-TNFi were three times more likely to attain a sustained clinical response, regardless of whether they had discontinued the first biologic due to a primary or secondary inefficacy.